La figure du tout intégré et les noms discrets collectifs - Viviane Arigne (Anglophonia)
This article assesses the role of the model of the integrated whole in the linguistics of collective nouns and, more particularly, collective discrete nouns. The cognitive dimension of the integrated whole whose prototype is given by the discrete noun body is twofold and concerns both metalinguistic and linguistic referential constructions. A number of features are isolated in the prototypical integrated whole, such as meronomical features, tri-dimensional object-reference, token-reference as well as position in the hierarchy of integrated wholes. Collective discrete nouns are analysed along the same lines as less prototypical integrated wholes. Isomorphism between a discrete whole and similarly discrete homeomerous parts accounts for the fascination collective discrete nouns hold for scholars, be it in English or French linguistics. The features pertaining to prototypical or collective integrated wholes help explain how collective mass-nouns are very frequently excluded from the class of collective nouns and how a number of collective discrete nouns are hardly ever mentioned in linguistic or grammatical works. Lastly, the noun body is analysed as a semantically derived collective noun: the prototypical integrated whole is used as a collective, less prototypical, integrated whole to unite and interlock the most independent discrete entities, human animates.